Count data modelling of health insurance and health care utilisation in Nigeria - Olayiwola Saheed O.; Kazeem Bayo L.O. (Journal of Economics and Management, 2019)
Aim/purpose – Estimation of the model of interdependent demand for health insurance and health care utilisation involves issues of stochastic dependence between health insurance and health care utilisation. This study explored a count data estimation technique to determine the most appropriate estimation method for the interdependence of health insurance and health care demand in Nigeria.